Evidence of a New Population of Weak Terrestrial Gamma‐Ray Flashes Observed From Aircraft Altitude - I. Bjørge‐Engeland; N. Østgaard; D. Sarria; M. Marisaldi; A. Mezentsev; A. Fuglestad; N. Lehtinen; J. E. Grove; D. Shy; T. Lang; M. Quick; H. Christian; et al. (Geophysical Research Letters)
Abstract Terrestrial Gamma‐ray Flashes (TGFs) are ten‐to‐hundreds of microsecond bursts of gamma‐rays produced when electrons in strong electric fields in thunderclouds are accelerated to relativistic energies. Space instruments have observed TGFs with source photon brightness down to ∼1017–1016. Based on space and aircraft observations, TGFs have been considered rare phenomena produced in association with very few lightning discharges. Space observations associated with lightning ground observations in the radio band have indicated that there exists a population of dimmer TGFs. Here we show observations of TGFs from aircraft altitude that were not detected by a space instrument viewing the same area. The TGFs were found through Monte Carlo modeling to be associated with 1015–1012 photons at source, which is several orders of magnitude below what can be seen from space. Our results suggest that there exists a significant population of TGFs that are too weak to be observed from space.